2021
DOI: 10.1021/acs.joc.1c01605
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical-Promoted Monochloroalkylarylation of Alkenes with Chloralkanes

Abstract: Free radical-initiated cascade cyclization of unactivated alkenes with chloralkanes, which undergoes selective activation of the α-C(sp 3 )−H bond of chloralkanes, provides a protocol for the synthesis of chlorinated heterocycles or polycyclic compounds. A series of radical inhibition experiments, radical capture operations, and radical clock tests were studied in this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…86 Intriguingly, in 2021, Liu, Li and coworkers reported the transposition of N -allylbenzamides or N -arylbut-3enamides to chlorinated dihydroisoquinolinones or dihydroquinolinone initiated by the C-radical generated from monochloroalkane, which is an uncommon C(sp 3 )–H functionalization reagent (Scheme 42). 87…”
Section: Intermolecular Cyclization Initiated By Directed C(sp3)–h Ox...mentioning
confidence: 99%
“…86 Intriguingly, in 2021, Liu, Li and coworkers reported the transposition of N -allylbenzamides or N -arylbut-3enamides to chlorinated dihydroisoquinolinones or dihydroquinolinone initiated by the C-radical generated from monochloroalkane, which is an uncommon C(sp 3 )–H functionalization reagent (Scheme 42). 87…”
Section: Intermolecular Cyclization Initiated By Directed C(sp3)–h Ox...mentioning
confidence: 99%
“…Secondly, although Chuang et al reported the unique example of using N-allylbenzamides for 1,4-aryl migration, these substrates have mainly been explored for constructing dihydroisoquinolinone derivatives via radical 6endo cyclization. [12] For instance, Wang and Li et al devised the photocatalytic oxidative radical cyclization of N-allyl benzamides with 2 a for the assembly of trifluoromethylated dihydroisoquinolinones. [12b] Therefore, we questioned whether meticulous examinations of reaction parameters would allow to identify an efficient electrochemical system capable of selectively favour the 5-exo cyclization of the βamino radical over the competitive 6-endo cyclization to promote the desired 1,4-aryl migration (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…8–10 Despite the above-mentioned critical achievements, studies on the synthesis of vinyl thiocyanates with simple and available terminal alkynes as initial materials are still in demand. Based on our previous radical cascade study, 11 we speculated whether aryl terminal alkynes could participate in radical addition and tandem cyclization in one pot and produce large exocyclic vinyl thiocyanates under mild and metal-free conditions (Scheme 1b).…”
mentioning
confidence: 99%